Hostname: page-component-745bb68f8f-hvd4g Total loading time: 0 Render date: 2025-02-10T10:52:15.661Z Has data issue: false hasContentIssue false

AN ANALOGUE OF AN IDENTITY OF JACOBI

Published online by Cambridge University Press:  07 February 2025

HENG HUAT CHAN
Affiliation:
Mathematics Research Center, Shandong University, No. 1 Building, 5 Hongjialou Road, Jinan 250100, P.R. China e-mail: chanhh6789@sdu.edu.cn
SONG HENG CHAN*
Affiliation:
Division of Mathematical Sciences, School of Physical and Mathematical Sciences, Nanyang Technological University, 21 Nanyang link, Singapore 637371, Republic of Singapore
PATRICK SOLÉ
Affiliation:
I2M (CNRS, University of Aix-Marseille), 163 Av. de Luminy, 13 009 Marseilles, France e-mail: sole@enst.fr
Rights & Permissions [Opens in a new window]

Abstract

H. H. Chan, K. S. Chua and P. Solé [‘Quadratic iterations to $\pi $ associated to elliptic functions to the cubic and septic base’, Trans. Amer. Math. Soc. 355(4) (2002), 1505–1520] found that, for each positive integer d, there are theta series $A_d, B_d$ and $C_d$ of weight one that satisfy the Pythagoras-like relationship $A_d^2=B_d^2+C_d^2$. In this article, we show that there are two collections of theta series $A_{b,d}, B_{b,d}$ and $C_{b,d}$ of weight one that satisfy $A_{b,d}^2=B_{b,d}^2+C_{b,d}^2,$ where b and d are certain integers.

Type
Research Article
Copyright
© The Author(s), 2025. Published by Cambridge University Press on behalf of Australian Mathematical Publishing Association Inc.

1 Introduction

One of the most famous identities of Jacobi states that

(1.1) $$ \begin{align} \bigg(\sum_{m,n=-\infty}^\infty q^{m^2+n^2}\bigg)^2=\bigg(\sum_{m,n=-\infty}^\infty (-1)^{m+n} q^{m^2+n^2}\bigg)^2+\bigg(\sum_{m,n=-\infty}^\infty q^{(m+1/2)^2+(n+1/2)^2}\bigg)^2. \end{align} $$

One can view (1.1) as a solution to

(1.2) $$ \begin{align} A^2=B^2+C^2, \end{align} $$

where $A,B$ and C are theta series of weight one. This identity is instrumental in the parametrisation of Gauss’ arithmetic–geometric mean by modular forms [Reference Borwein and Borwein2, Reference Solé and Loyer8].

In [Reference Chan, Chua and Solé5], Chan et al., motivated by the study of codes and lattices, found that, for any positive integer d,

(1.3) $$ \begin{align} \bigg(\sum_{m,n=-\infty}^\infty q^{2(m^2+mn+dn^2)}\bigg)^2 & =\bigg(\sum_{m,n=-\infty}^\infty (-1)^{m+n} q^{m^2+mn+dn^2}\bigg)^2 \notag \\ &\quad +\bigg(\sum_{m,n=-\infty}^\infty q^{2((m+1/2)^2+(m+1/2)n+dn^2)}\bigg)^2. \end{align} $$

Identity (1.3) provides an infinite number of solutions in theta functions of weight one to (1.2). For more information on this generalised Jacobi identity, see [Reference Chan, Chua and Solé6, Reference Chua and Solé7].

Recently, while studying theta series associated with binary quadratic forms of discriminant $-15$ , we discovered the identity

(1.4) $$ \begin{align} \bigg(\sum_{m,n=-\infty}^\infty q^{2m^2+mn+2n^2}\bigg)^2 & = \bigg(\sum_{m,n=-\infty}^\infty (-1)^{m+n} q^{2m^2+mn+2n^2}\bigg)^2 \notag \\ &\quad +\bigg(2\sum_{m,n=-\infty}^\infty q^{2(2(m+1/2)^2+(m+1/2)n+2n^2)}\bigg)^2. \end{align} $$

We establish the following analogue of (1.3) for which (1.4) is a special case.

Theorem 1.1. Let d be any positive integer and let $1\leq b\leq d-1$ . Then

(1.5) $$ \begin{align} \bigg(\sum_{m,n=-\infty}^\infty q^{dm^2+bmn+dn^2} \bigg)^2 &=\bigg(\sum_{m,n=-\infty}^\infty (-1)^{m+n} q^{dm^2+bmn+dn^2}\bigg)^2 \notag \\ &\quad + \bigg(2\sum_{m,n=-\infty}^\infty q^{2(d(m+1/2)^2+b(m+1/2)n+dn^2)}\bigg)^2. \end{align} $$

When $d=2$ and $b=1$ , we recover (1.4) from (1.5). The proof of (1.5) is given in Section 2.

Our discovery of (1.5) provides a motivation for deriving the following two-variable version of (1.3): that is,

(1.6) $$ \begin{align} \bigg(\sum_{m,n=-\infty}^\infty q^{2(bm^2+bmn+dn^2)}\bigg)^2 & =\bigg(\sum_{m,n=-\infty}^\infty (-1)^{m+n} q^{bm^2+bmn+dn^2}\bigg)^2 \notag \\ &\quad +\bigg(\sum_{m,n=-\infty}^\infty q^{2(b(m+1/2)^2+b(m+1/2)n+dn^2)}\bigg)^2. \end{align} $$

Observe that, when $b=1$ , (1.6) implies (1.3). We give a proof of (1.6) in Section 3.

2 Proof of (1.5)

The Jacobi one-variable theta functions are defined by

$$ \begin{align*} \vartheta_2(q) &= \sum_{j=-\infty}^\infty q^{(j+1/2)^2},\\ \vartheta_3(q) &= \sum_{j=-\infty}^\infty q^{j^2}\end{align*} $$

and

$$ \begin{align*} \vartheta_4(q) &= \sum_{j=-\infty}^\infty (-1)^jq^{j^2}. \end{align*} $$

We first express the theta functions in (1.5) in terms of $\vartheta _j(q), j=2,3,4$ .

Lemma 2.1. For $|q|<1$ ,

(2.1) $$ \begin{align} &\mathcal A_{b,d}=\sum_{m,n=-\infty}^\infty q^{dm^2+bmn+dn^2} = \vartheta_3(q^{2d+b})\vartheta_3(q^{2d-b}) +\vartheta_2(q^{2d+b})\vartheta_2(q^{2d-b}),\quad\qquad \end{align} $$
(2.2) $$ \begin{align} &\mathcal B_{b,d}=\sum_{m,n=-\infty}^\infty (-1)^{m+n}q^{dm^2+bmn+dn^2} = \vartheta_3(q^{2d+b})\vartheta_3(q^{2d-b}) -\vartheta_2(q^{2d+b})\vartheta_2(q^{2d-b}) \end{align} $$

and

(2.3) $$ \begin{align} &\mathcal C_{b,d}=2\sum_{m,n=-\infty}^\infty q^{2(d(m+1/2)^2+b(m+1/2)n+dn^2)} = \vartheta_2(q^{d+b/2})\vartheta_2(q^{d-b/2}). \end{align} $$

Proof. We observe that

$$ \begin{align*}dm^2+bmn+dn^2 =\begin{pmatrix} m & n \end{pmatrix}\begin{pmatrix} d & b/2 \\ b/2 & d\end{pmatrix} \begin{pmatrix} m \\ n \end{pmatrix}.\end{align*} $$

Next, since

$$ \begin{align*}\begin{pmatrix} d & b/2 \\ b/2 & d\end{pmatrix} = \begin{pmatrix} 1 & 1 \\ 1 & -1 \end{pmatrix} \begin{pmatrix} d+b/2 & 0 \\ 0 & d-b/2 \end{pmatrix} \begin{pmatrix} 1 & 1 \\ 1 & -1 \end{pmatrix},\end{align*} $$

we find that

$$ \begin{align*}dm^2+bmn+dn^2 = \dfrac{2d+b}{4}(m+n)^2 +\dfrac{2d-b}{4}(m-n)^2.\end{align*} $$

Therefore,

$$ \begin{align*} &\sum_{m,n=-\infty}^\infty q^{dm^2+bmn+dn^2} = \sum_{m,n=-\infty}^\infty q^{(2d+b)(m+n)^2/4+(2d-b)(m-n)^2/4}\\ &\quad =\sum_{\substack{m,n=-\infty\\ m+n \text{ even}}}^\infty q^{(2d+b)(m+n)^2/4+(2d-b)(m-n)^2/4}+ \sum_{\substack{m,n=-\infty\\ m+n \text{ odd}}}^\infty q^{(2d+b)(m+n)^2/4+(2d-b)(m-n)^2/4}\\ &\quad =\vartheta_3(q^{2d+b})\vartheta_3(q^{2d-b})+\vartheta_2(q^{2d+b})\vartheta_2(q^{2d-b}), \end{align*} $$

which completes the proof of (2.1). The proof of (2.2) is similar to the proof of (2.1).

To prove (2.3), we need the identity

(2.4) $$ \begin{align} \sum_{m=-\infty}^\infty (-1)^mq^{(m+1/2)^2} = 0.\end{align} $$

Identity (2.4) is true because

$$ \begin{align*}\sum_{m=-\infty}^\infty (-1)^m q^{(m+1/2)^2} = \sum_{s=-\infty}^\infty (-1)^s q^{(s-1/2)^2} =\sum_{t=-\infty}^\infty (-1)^{t+1} q^{(t+1/2)^2}.\end{align*} $$

From (2.4), we deduce that, for any integer $\ell $ ,

(2.5) $$ \begin{align} \sum_{m=-\infty}^\infty (-1)^mq^{(m+\ell+1/2)^2} = 0.\end{align} $$

A consequence of (2.5) is that

(2.6) $$ \begin{align} \sum_{n=-\infty}^\infty q^{(2n+\ell+1/2)^2}=\sum_{n=-\infty}^\infty q^{(2n+1+\ell+1/2)^2}. \end{align} $$

We are now ready to prove (2.3). Write

$$ \begin{align*}\mathcal C_{b,d} = 2\sum_{m,n=-\infty}^\infty q^{(2d+b)(m+1/2+n)^2/2+(2d-b)(m+1/2-n)^2/2}.\end{align*} $$

Let $k=m-n.$ Then

$$ \begin{align*}\mathcal C_{b,d} &= 2\sum_{k=-\infty}^\infty q^{(2d-b)(k+1/2)^2/2}\sum_{n=-\infty}^\infty q^{(2d+b)(2n+k+1/2)^2/2}\\ &=\sum_{k=-\infty}^\infty q^{(2d-b)(k+1/2)^2/2}\sum_{s=-\infty}^\infty q^{(2d+b)(s+1/2)^2/2}=\vartheta_2(q^{(2d-b)/2})\vartheta_2(q^{(2d+b)/2}), \end{align*} $$

which is (2.3). The last equality follows by writing

$$ \begin{align*} 2\sum_{n=-\infty}^\infty q^{(2d+b)(2n+k+1/2)^2/2}&= \sum_{n=-\infty}^\infty q^{(2d+b)(2n+k+1/2)^2/2}+\sum_{n=-\infty}^\infty q^{(2d+b)(2n+k+1+1/2)^2/2}\\ &=\sum_{s=-\infty}^\infty q^{(2d+b)(s+1/2)^2/2}, \end{align*} $$

where we have used (2.6) in the first equality.

Using (2.1) and (2.2), we deduce that

$$ \begin{align*}\mathcal A_{b,d}^2 -\mathcal B_{b,d}^2 = 4\vartheta_2(q^{2d+b})\vartheta_2(q^{2d-b})\vartheta_3(q^{2d+b})\vartheta_3(q^{2d-b}) .\end{align*} $$

Next, it is known from Jacobi’s triple product identity that

$$ \begin{align*} \vartheta_2(q) = 2q^{1/4}\prod_{j=1}^\infty (1-q^{2j})(1+q^{2j})^2 \end{align*} $$

and

$$ \begin{align*}\vartheta_3(q) = \prod_{j=1}^\infty (1-q^{2j})(1+q^{2j-1})^2.\end{align*} $$

Therefore,

(2.7) $$ \begin{align} 2\vartheta_2(q^2)\vartheta_3(q^2) = \vartheta_2^2(q).\end{align} $$

Replacing $q^2$ by q and using (2.3), we deduce that

$$ \begin{align*}\mathcal A_{b,d}^2 -\mathcal B_{b,d}^2 =\mathcal C_{b,d}^2\end{align*} $$

and the proof of (1.5) is complete.

It is possible to derive (2.7) without using Jacobi’s triple product identity. For more details, see [Reference Chan4, page 58].

When $d=1$ and $b=0$ , (1.5) becomes

$$ \begin{align*} \bigg(\sum_{m,n=-\infty}^\infty q^{m^2+n^2} \bigg)^2 =\bigg(\sum_{m,n=-\infty}^\infty (-1)^{m+n} q^{m^2+n^2}\bigg)^2 + \bigg(2\sum_{m,n=-\infty}^\infty q^{2((m+1/2)^2+n^2)}\bigg)^2, \end{align*} $$

which reduces to

(2.8) $$ \begin{align} \vartheta_3^4(q)=\vartheta_4^4(q) + 4\vartheta_2^2(q^2)\vartheta_3^2(q^2).\end{align} $$

By (2.7), we arrive at (1.1). Next, (2.8) can then be written as

(2.9) $$ \begin{align}\vartheta_3^4(q)+\vartheta_2^4(q)=\vartheta_3^4(q)-\vartheta_2^4(q) + 8 \vartheta_2^2(q^2)\vartheta_3^2(q^2). \end{align} $$

Identity (2.9) appeared in [Reference Berndt, Chan and Liaw1, page 140] and the functions

$$ \begin{align*}\vartheta_3^4(q)+\vartheta_2^4(q), \quad \vartheta_3^4(q)-\vartheta_2^4(q) =\vartheta_4^4(q) \quad\text{and} \quad 2\vartheta_2^2(q)\vartheta_3^2(q)\end{align*} $$

play important roles in Ramanujan’s theory of elliptic functions to the quartic base (see [Reference Borwein and Borwein3, Theorem 2.6(b)] and [Reference Berndt, Chan and Liaw1, (1.10) and (1.11)]).

3 Proof of (1.6)

The proof of (1.6) is similar to the proof of (1.3). First, we need a lemma.

Lemma 3.1. Let $0< b<4d$ . Then

(3.1) $$ \begin{align} A_{b,d}&=\sum_{m,n=-\infty}^\infty q^{2(bm^2+bmn+dn^2)} = \vartheta_3(q^{2b})\vartheta_3(q^{2(4d-b)})+\vartheta_2(q^{2b})\vartheta_2(q^{2(4d-b)}), \end{align} $$
(3.2) $$ \begin{align}\ B_{b,d}&=\sum_{m,n=-\infty}^\infty (-1)^{m-n}q^{bm^2+bmn+dn^2} = \vartheta_4(q^{b})\vartheta_4(q^{4d-b})\qquad\qquad\qquad\qquad \end{align} $$

and

(3.3) $$ \begin{align} C_{b,d}&=\sum_{m,n=-\infty}^\infty q^{2(b(m+1/2)^2+b(m+1/2)n+dn^2)}=\vartheta_2(q^{2b})\vartheta_3(q^{2(4d-b)})+ \vartheta_3(q^{2b})\vartheta_2(q^{2(4d-b)}). \end{align} $$

Proof. The proof of (3.1) follows by writing $A_{b,d}$ as

$$ \begin{align*} A_{b,d} = \sum_{m,n=-\infty}^\infty q^{2b(m+n/2)^2+n^2(4d-b)/2}. \end{align*} $$

Splitting the sum into two sums with one summing over even integers $n=2\ell $ and the other summing over odd integers $n=2\ell +1$ , we find that

$$ \begin{align*} A_{b,d} &= \sum_{m,\ell=-\infty}^\infty q^{2b(m+\ell)^2+2\ell^2(4d-b)}+ \sum_{m,\ell=-\infty}^\infty q^{2b(m+\ell+1/2)^2+2(\ell+1/2)^2(4d-b)}\\ &=\vartheta_3(q^{2b})\vartheta_3(q^{2(4d-b)})+\vartheta_2(q^{2b})\vartheta_2(q^{2(4d-b)}), \end{align*} $$

and this completes the proof of (3.1). Next, write $B_{b,d}$ as

$$ \begin{align*}B_{b,d} = \sum_{m,n=-\infty}^\infty (-1)^{m-n} q^{b(m+n/2)^2+n^2(4d-b)/4}.\end{align*} $$

Splitting the sum into two sums with one summing over even integers $n=2\ell $ and the other summing over odd integers $n=2\ell +1$ and using (2.5), we find that

$$ \begin{align*} B_{b,d} &= \sum_{m,\ell=-\infty}^\infty (-1)^m q^{2b(m+\ell)^2+2\ell^2(4d-b)}+ \sum_{m,\ell=-\infty}^\infty q^{2b(m+\ell+1/2)^2+2(\ell+1/2)^2(4d-b)}\\ &=\sum_{m,\ell=-\infty}^\infty (-1)^\ell q^{(4d-b)\ell^2}\sum_{m=-\infty}^\infty (-1)^{m+\ell} q^{b(m+\ell)^2}\\ &=\vartheta_4(q^{4d-b})\vartheta_4(q^b), \end{align*} $$

and (3.2) follows. Finally, to prove (3.3), write

$$ \begin{align*} C_{b,d} = \sum_{m,n=-\infty}^\infty q^{2 b(m+1/2+n/2)^2+2n^2(4d-b)/4}. \end{align*} $$

Splitting the sum into two sums with one summing over even integers $n=2\ell $ and the other summing over odd integers $n=2\ell +1$ , we deduce that

$$ \begin{align*} C_{b,d} &= \sum_{m,\ell=-\infty}^\infty q^{2b(m+\ell+1/2)^2+2(2\ell)^2(4d-b)/4}+ \sum_{m,\ell=-\infty}^\infty q^{2b(m+\ell+1)^2+2(2\ell+1)^2(4d-b)/4}\\ &=\vartheta_2(q^{2b})\vartheta_3(q^{8d-2b})+\vartheta_3(q^{2b})\vartheta_2(q^{8d-2b}), \end{align*} $$

and the proof of (3.3) is complete.

To complete the proof of (1.6), we note that

$$ \begin{align*}A_{b,d}-C_{b,d} = (\vartheta_3(q^{2b})-\vartheta_2(q^{2b})) (\vartheta_3(q^{8d-2b})-\vartheta_2(q^{8d-2b}))\end{align*} $$

and

$$ \begin{align*}A_{b,d}+C_{b,d} = (\vartheta_3(q^{2b})+\vartheta_2(q^{2b})) (\vartheta_3(q^{8d-2b})+\vartheta_2(q^{8d-2b})).\end{align*} $$

But it is immediate that

$$ \begin{align*}\vartheta_3(q^4)-\vartheta_2(q^4) = \vartheta_4(q)\end{align*} $$

and

$$ \begin{align*}\vartheta_3(q^4)+\vartheta_2(q^4) = \vartheta_3(q).\end{align*} $$

Therefore,

$$ \begin{align*}(\vartheta_3(q^4)-\vartheta_2(q^4))(\vartheta_3(q^4)+\vartheta_2(q^4))= \vartheta_4(q)\vartheta_3(q)=\vartheta_4^2(q^2),\end{align*} $$

where the last equality follows from [Reference Borwein and Borwein2, page 34]. Therefore,

$$ \begin{align*} A_{b,d}^2-C_{b,d}^2& = (\vartheta_3(q^{2b})-\vartheta_2(q^{2b})) (\vartheta_3(q^{8d-2b})-\vartheta_2(q^{8d-2b}))\\ &\quad\times (\vartheta_3(q^{2b})+\vartheta_2(q^{2b})) (\vartheta_3(q^{8d-2b})+\vartheta_2(q^{8d-2b}))\\ &=\vartheta_4^2(q^b)\vartheta_4^2(q^{4d-b})=B_{b,d}^2, \end{align*} $$

and the proof of (1.6) is complete.

4 Concluding remarks

We have found infinitely many solutions to $X^2+Y^2=Z^2$ , where $X,Y$ and Z are theta series of weight one. The Borweins’ identity states that

(4.1) $$ \begin{align} \bigg(\sum_{m,n=-\infty}^\infty q^{m^2+mn+n^2}\bigg)^3 &=\bigg(\sum_{m,n=-\infty}^\infty \omega^{m-n}q^{m^2+mn+n^2}\bigg)^3 \notag \\ &\quad +\bigg(\sum_{m,n=-\infty}^\infty q^{(m+1/3)^2+(m+1/3)(n+1/3)+(n+1/3)^2}\bigg)^3, \end{align} $$

where $\omega =e^{2\pi i/3}.$ This is the only example of a solution to $X^3+Y^3=Z^3$ with X, Y and Z being theta series of weight one. Are there infinitely many solutions to $X^3+Y^3=Z^3$ , where $X,Y$ and Z are theta series of weight one, apart from (4.1)? This appears to be an interesting question.

Footnotes

The second author is partially supported by the Ministry of Education, Singapore, Academic Research Fund, Tier 1 (RG15/23).

References

Berndt, B. C., Chan, H. H. and Liaw, W.-C., ‘On Ramanujan’s quartic theory of elliptic functions’, J. Number Theory 88(1) (2001), 129156.CrossRefGoogle Scholar
Borwein, J. M. and Borwein, P. B., $\pi$ and the AGM: A Study in Analytic Number Theory and Computational Complexity (Wiley, Chichester, 1987).Google Scholar
Borwein, J. M. and Borwein, P. B., ‘A cubic counterpart of Jacobi’s identity and the AGM’, Trans. Amer. Math. Soc. 323(2) (1991), 691701.Google Scholar
Chan, H. H., Theta Functions, Elliptic Functions and $\pi$ (De Gruyter, Berlin–Boston, 2020).CrossRefGoogle Scholar
Chan, H. H., Chua, K. S. and Solé, P., ‘Quadratic iterations to $\pi$ associated to elliptic functions to the cubic and septic base’, Trans. Amer. Math. Soc. 355(4) (2002), 15051520.CrossRefGoogle Scholar
Chan, H. H., Chua, K. S. and Solé, P., ‘Seven modular lattices and a septic base Jacobi identity’, J. Number Theory 99(2) (2003), 361372.CrossRefGoogle Scholar
Chua, K. S. and Solé, P., ‘Jacobi identities, modular lattices, and modular towers’, European J. Combin. 25(4) (2004), 495503.CrossRefGoogle Scholar
Solé, P. and Loyer, P., ‘ ${U}_n$ lattices, construction $B$ , and AGM iterations’, European J. Combin. 19(2) (1998), 227236.CrossRefGoogle Scholar